Interaction of antidiabetic α‐glucosidase inhibitors and gut bacteria α‐glucosidase - Tan, Kemin (Protein Sci, 2018)
Carbohydrate hydrolyzing α‐glucosidases are commonly found in microorganisms present in the human intestine microbiome. We have previously reported crystal structures of an α‐glucosidase from the human gut bacterium Blaubia (Ruminococcus) obeum (Ro‐αG1) and its substrate preference/specificity switch. This novel member of the GH31 family is a structural homolog of human intestinal maltase‐glucoamylase (MGAM) and sucrase–isomaltase (SI) with a highly conserved active site that is predicted to be common in Ro‐αG1 homologs among other species that colonize the human gut. In this report, we present structures of Ro‐αG1 in complex with the antidiabetic α‐glucosidase inhibitors voglibose, miglitol, and acarbose and supporting binding data. The in vitro binding of these antidiabetic drugs to Ro‐αG1 suggests the potential for unintended in vivo crossreaction of the α‐glucosidase inhibitors to bacterial α‐glucosidases that are present in gut microorganism communities. Moreover, analysis of these drug‐bound enzyme structures could benefit further antidiabetic drug development.